Environmental enrichment promotes resilience to neuropathic pain-induced depression and correlates with decreased excitability of the anterior cingulate cortex - Falkowska, Marta; Ntamati, Niels R.; Nevian, Natalie E.; Nevian, Thomas; Acuña, Mario A. (Frontiers in Behavioral Neuroscience, 2023)
Depression is a common comorbidity of chronic pain with many patients being affected. However, efficient pharmacological treatment strategies are still lacking. Therefore, it is desirable to find additional alternative approaches. Environmental enrichment has been suggested as a method to alleviate pain-induced depression. However, the neuronal mechanisms of its beneficial effects are still elusive. The anterior cingulate cortex (ACC) plays a central role in processing pain-related negative affect and chronic pain-induced plasticity in this region correlates with depressive symptoms. We studied the consequences of different durations of environmental enrichment on pain sensitivity and chronic pain-induced depression-like behaviors in a mouse model of neuropathic pain. Furthermore, we correlated the behavioral outcomes to the activity levels of pyramidal neurons in the ACC by analyzing their electrophysiological properties ex vivo. We found that early exposure to an enriched environment alone was not sufficient to cause resilience against pain-induced depression-like symptoms. However, extending the enrichment after the injury prevented the development of depression and reduced mechanical hypersensitivity. On the cellular level, increased neuronal excitability was associated with the depressive phenotype that was reversed by the enrichment. Therefore, neuronal excitability in the ACC was inversely correlated to the extended enrichment-induced resilience to depression. These results suggest that the improvement of environmental factors enhanced the resilience to developing chronic pain-related depression. Additionally, we confirmed the association between increased neuronal excitability in the ACC and depression-like states. Therefore, this non-pharmacological intervention could serve as a potential treatment strategy for co-morbid symptoms of chronic pain.